SLOW DEEP BREATHING EXERCISE ON PATIENTS’ BLOOD PRESSURE WITH HYPERTENSION IN WORKING AREA OF KERTOSARI HEALTH CENTER BANYUWANGI 2020 - Rima Ambarwati; Masroni; Anita Dwi Ariyani (Bajang Institute, 2021)
Slow deep breathing exercise is a non-pharmacological therapy in hypertension patients without comorbidities that can reduce blood pressure. This study aimed to investigate the effect of slow deep breathing exercise on patients’ blood pressure with hypertension in working area of Kertosari Health Center Banyuwangi. This study used experimental design with One-Group Pre-test - Post-test. The sample consisted of 11 respondents who fit the inclusion criteria recruited from an observation sheet of blood pressure measurement using a digital sphygmomanometer, then processed by conducting scoring, tabulating and statistical analysis using Paired T-Test from SPSS 25 for windows. The average respondent's SBP (Systolic Blood Pressure) before SDB (slow deep breathing) was 162.82 mmHg and after SDB was 133.27 mmHg. The average DBP before SDB was 87.91 mmHg and after SDB was 80.09 mmHg. Further analysis used Paired T-Test found ρ value = 0.000, α = 0.05 or ρ value < 0.05. It can be concluded that there was a significant Effect of Slow Deep Breathing Exercise on Patients' Blood Pressure with Hypertension in Working Area of Kertosari Health Center Banyuwangi 2020.